A talented giant: a tribute to the memory of John M. Opitz - Lorenzo Pavone; Giovanni Corsello; Martino Ruggieri (Italian Journal of Pediatrics, 2024)
Abstract Background John M. Opitz, a towering figure in both stature and scientific achievement, left an indelible mark on the fields of genetics, pediatrics, and embryology. Born in 1935 in Hamburg to a Jewish family, Opitz’s early life was marked by adversities. Despite these challenges, he pursued a remarkable career, immigrating to the United States at 15 years and becoming a renowned scientist in institutions like Iowa State University and the University of Wisconsin, where he made groundbreaking contributions to clinical genetics. Main body A testament to his compassionate nature, Opitz dedicated himself to understanding and treating rare genetic disorders, earning him eponymous recognition in several medical conditions. His impact extended beyond academia, as evidenced by his collaborative efforts with Sicilian universities to advance clinical genetics in Italy. Opitz’s teaching style emphasized simplicity, empathy, and meticulous clinical examination, leaving an indelible mark on students and colleagues. Conclusion John M. Opitz’s towering intellect, compassionate demeanor, and profound impact on medicine and genetics made him a figure of enduring significance. His legacy lives on through the countless lives he touched, the knowledge he transmitted, and the enduring friendships he forged. In remembering John Opitz, we honor not only a man, but also a myth—a symbol of resilience, humanity, and scientific excellence.